A Network Utilization Perspective on the Leadership Advancement of Minorities - Khattab, Jasmien; van Knippenberg, Daan; Pieterse, Anne Nederveen; Hernandez, Morela (Academy of Management Review, 2020)
Social network researchers have shown that, compared to their effect on majority employees, structural constraints can cause minority employees to end up in network positions that limit their access to resources (i.e., social capital) and that consequently limit their access to professional opportunities. These findings, however, do not explain why structurally equivalent minority and majority employees achieve differential returns of social capital on their leadership advancement. We propose that majority and minority employees differ in terms of network utilization, which is the extent to which individuals utilize their existing network ties. We theorize why and how network utilization processes—career and work utilization of network ties—can explain employees’ (i.e., actors) influence on their leadership advancement. We also explicate the process through which actors’ direct and indirect network connections (i.e., alters) contribute to such outcomes through both career-supporting utilization and work-supporting utilization with actors. We conclude by outlining the boundary conditions of network utilization theory, a theory that changes the current understanding of how existing social network ties can perpetuate the underrepresentation of minorities in leadership positions.